Breastfeeding, lung volumes and alveolar size at school-age. Issue 1 (6th July 2015) - Dogaru, Cristian M; Narayanan, Manjith; Spycher, Ben D; Pescatore, Anina M; Owers-Bradley, John; Beardsmore, Caroline S; Silverman, Michael; Kuehni, Claudia E
Abstract : Background: Previous studies found larger lung volumes at school-age in formerly breastfed children, with some studies suggesting an effect modification by maternal asthma. We wanted to explore this further in children who had undergone extensive lung function testing. The current study aimed to assess whether breastfeeding was associated with larger lung volumes and, if so, whether all compartments were affected. We also assessed association of breastfeeding with apparent diffusion coefficient (ADC), which measures freedom of gas diffusion in alveolar-acinar compartments and is a surrogate of alveolar dimensions. Additionally, we assessed whether these effects were modified by maternal asthma. Methods: We analysed data from 111 children and young adults aged 11–21 years, who had participated in detailed lung function testing, including spirometry, plethysmography and measurement of ADC of 3 Helium ( 3 He) by MR. Information on breastfeeding came from questionnaires applied in early childhood (age 1–4 years). We determined the association between breastfeeding and these measurements using linear regression, controlling for potential confounders. Results: We did not find significant evidence for an association between duration of breastfeeding and lung volumes or alveolar dimensions in the entire sample. In breastfed children of mothers with asthma, we observed larger lung volumes and larger average alveolar size than in non-breastfed children, but the differences did not reach significance levels. Conclusions: Confirmation of effects of breastfeeding on lung volumes would have important implications for public health. Further investigations with larger sample sizes are warranted.